2016
DOI: 10.1016/j.jchromb.2016.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of brown dog tick repellents, 2-hexanone and benzaldehyde, and release from tick-resistant beagles, Canis lupus familiaris

Abstract: We have recently shown that repellency of the tick Rhipicephalus sanguineus sensu lato by the tick resistant dog breed, the beagle, is mediated by volatile organic compounds (VOCs) 2-hexanone and benzaldehyde present in beagle odour. Ectoparasite location of animal hosts is affected by variation in these odour components and their ratios. The aim of this study was to quantify the release rate, and the ratio, of 2-hexanone and benzaldehyde from beagles. The odour of three beagles was collected, for four days, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
(50 reference statements)
3
7
0
1
Order By: Relevance
“…comm.). Similar results have been reported for differential attractiveness of different dog breeds to ticks (Borges et al 2015;de Oliveira Filho et al 2016, with the same hypothesis of differential volatile signalling testing true, albeit the repellents that were identified were different from those in cattle.…”
Section: Volatile Semiochemicalssupporting
confidence: 84%
“…comm.). Similar results have been reported for differential attractiveness of different dog breeds to ticks (Borges et al 2015;de Oliveira Filho et al 2016, with the same hypothesis of differential volatile signalling testing true, albeit the repellents that were identified were different from those in cattle.…”
Section: Volatile Semiochemicalssupporting
confidence: 84%
“…Our subsequent work identified two volatile small lipophilic molecules(SLMs), 2-hexanone and benzaldehyde,which are produced in greater amounts in beagles,and which act as natural 4 4 repellents against R. sanguineuss. l. (Borges et al, 2015), and demonstrated constitutive release of these two SLMs in the odor of beagles (Oliveira Filho et al, 2016).…”
Section: Introduction 3mentioning
confidence: 93%
“…The oven temperature was maintained at 30 o C for 0.1 min, then programmed at 10 o C min −1 to 250 o C and held for 30 min. The quantity of compound captured per sample was expressed in µg/day using the analytical method described by Oliveira-Filho et al (2016). For 15 days, the release rates were 30.44 ± 1.12 µg/day for benzaldehyde and 14.38 ± 1.26 µg/day for 2-hexanone, decreasing sharply to 11.18 µg/day and 1.29 µg/day, respectively, after the 7 th day.…”
Section: Preparation and Use Of Prototype Non-host Semiochemical Delimentioning
confidence: 99%
“…Although a few studies have demonstrated that host VOCs play a role in attracting Rhipicephalus spp. ticks (Louly et al, 2010 ; Borges et al, 2015 ; de Oliveira Filho et al, 2016 ; Franzin et al, 2017 ), research is still needed to investigate the interrelationship of host microbiota with VOC production related with tick attraction or repulsion. This may potentially reveal yet other factors contributing to tick susceptibility thereby presenting new opportunities to develop control methods for the livestock ectoparasite, R. microplus .…”
Section: Microbiota Role In Tick Resistancementioning
confidence: 99%